Negative Impoliteness Strategies Used by Customers of Muara Bungo Home Credit - Rini Afrilesa J; Vera Magria (Jurnal Ilmiah Pendidikan Scholastic, 2023)
This research analyzes the negative impoliteness strategies used by customers of Muara Bungo Home Credit through WhatsApp text messages and how the strategies function in delivering the impoliteness between the customers and the employees of Home Credit. The purposes of this research are (1) to analyze the negative of impoliteness strategies used by customers of Muara Bungo Home Credit; (2) to analyze the functions of impoliteness strategies aimed by customers of Muara Bungo Home Credit. The analysis applied Culpeper’s (1996) theory on impoliteness strategy and Culpeper’s (2011) theory on impoliteness function. The research also applied descriptive qualitative method, with the customers’ WhatsApp text messages as the source of the data. The result of this research shows that, (1) there are negative impoliteness (6 data) which occurred in the research; (2) all 6 data of negative impoliteness strategies used by the customers had different functions, which are affective (3 data), and coercive (3 data).